Boron Nitride doped Chitosan Functionalized Graphene for an Efficient Dye Degradation. Issue 31 (17th August 2021) - Khose, Rahul V.; Lokhande, Kshama D.; Bhakare, Madhuri A.; Dhumal, Pratik S.; Wadekar, Pravin H.; Some, Surajit
Abstract: In this article, we have developed a simple and highly effective method for synthesis of boron nitride, chitosan and graphene‐based composite (BNCG). The BNCG has been synthesized by using cheap precursors such as boric acid, melamine, chitosan, and graphene oxide in a seal tube under nitrogen atmosphere and applied to degrade methylene blue. The dye degradation of methylene blue (MB) and Acid orange II (AO II) has been carried out using sunlight. The effective degradation of dye takes place at basic pH. The 10, 25, and 50 ppm of dye has successfully degraded in 10 min. of time. The degradation study concluded that about 87 % of the MB and 57 % AO II dye were degraded by BNCG composite. The degradation follows the first order kinetics as per the observed results. This preparative method and BNCG composite will overcome complicated preparative steps and a long time for dye degradation. Abstract : The present work is based on the synthesis of boron nitride, chitosan and graphene‐based composite called as BNCG. The resultant composite had shown great application in the field of dye degradation. To check BNCG composite efficiency, we carried out the degradation study for 50 ml of 50 ppm methylene blue and acid orange II dyes under sunlight. Methylene blue and acid orange II dyes were degraded up to 87 and 57 % by BNCG composite within 10 and 20 min, respectively.